Espacialidad sagrada: devoción popular a Santa Raimunda, alma do Bom Sucesso. - DOURADO DA SILVA, RACHEL (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Santa Raimunda do Bom Sucesso is a popular religious reference of the residents of the Amazon rainforest, especially of the locality of Bom Sucesso, seringal Icuriã in the Chico Mendes Extractivist Reserve. The objective of this work is to present the motivations and stimuli for cornering in the territory, as well as the links of people with space through social markers that configure sacred spatialities and build social relationships. Cultural manifestations in the historical context of territorialization in the region. Faced with the infinite absences, these are used as tools to survive, resist and resignify their lives in the face of different difficulties and new spatialities, supported by popular beliefs. The research is geographical and uses support from other areas of the sciences for theoretical organization such as anthropology and history; Phenomenology is the immersion path for understanding the phenomenon of popular devotion in relation to community dynamics, as a result if you observe that popular devotions are an essential element in the processes of social organization in the jungle.